2001
DOI: 10.1002/arch.1061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium channel antagonists on the corpora allata of adult male loreyi leafworm Mythimna loreyi: Juvenile hormone acids release and intracellular calcium level

Abstract: The effects of voltage-dependent calcium channel (VDCC) antagonists and the non-specific calcium channel antagonists on both juvenile hormone acids (JHA) release and cytosolic free calcium concentration ([Ca2+]i) are investigated in the corpora allata (CA) of the adult males loreyi leafworm Mythimna loreyi. The VDCC antagonists used in this study are: the L-type antagonists diltiazem, nifedipine, and verapamil, the N-type antagonist omega-Conotoxin (CgTx) GVIA, the N- and P/Q-type antagonist omega-CgTx MVIIC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This study addition of inorganic Ca 2+ channel blockers (Cd 2+ or Co 2+ ) was used to demonstrate the Ca 2+ dependence of  Ca 2+ -activated k + currents [94]. Cd 2+ and Co 2+ were the nonspecific calcium channel antagonists in the study [95, 96]. Co 2+ did not modify significantly the ATP-evoked current [97].…”
Section: The Mechanism By Which CD Affects Cnsmentioning
confidence: 99%
“…This study addition of inorganic Ca 2+ channel blockers (Cd 2+ or Co 2+ ) was used to demonstrate the Ca 2+ dependence of  Ca 2+ -activated k + currents [94]. Cd 2+ and Co 2+ were the nonspecific calcium channel antagonists in the study [95, 96]. Co 2+ did not modify significantly the ATP-evoked current [97].…”
Section: The Mechanism By Which CD Affects Cnsmentioning
confidence: 99%
“…The non-specific Ca 2+ channel blockers Ni 2+ and Co 2+ (for reference see Hsieh et al, 2001) induced a significant decrease in the fluorescence ratio, indicating a decline of [Ca 2+ ] i . A first significant inhibition was observed at a concentration of 5 Â 10 À 4 mol l À 1 (Fig.…”
Section: Depolarization Experimentsmentioning
confidence: 99%
“…Since we have demonstrated that the ETH-JH signaling cascade is required for courtship LTM and that augmented Inka cell activity during the training session improves LTM performance (Figure 1), we also asked whether augmented CA activity through expression of dTrpA1 would enhance courtship LTM via increased JH levels. Previous studies showed that Ca 2+ influx induces biosynthesis and release of JH in the CA (Kikukawa et al, 1987;Yamamoto et al, 1988;Allen et al, 1992;Hsieh et al, 2001;Chiang et al, 2002). We expressed dTrpA1 in the CA using the JHAMT-GAL4 driver, since this would be expected to depolarize CA cells.…”
Section: An Eth-jh Signaling Cascade Regulates Courtship Ltmmentioning
confidence: 99%